ORGANIZATIONAL CULTURE WITH EMPLOYEE WORK MOTIVATION OF CV X - Sustiyana Maelani Ade Kusuma; Sutarto Wijono (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to find out how the relationship between organizational culture and employee motivation at CV X in the packing section is related to one another. The author uses a quantitative method in this study, which has a total population and a sample of 60 respondents taken from all employees of the packing section. This study uses the help of SPSS version 2.5 for Windows and uses a saturated sampling technique. The instrument for measuring organizational culture in this study uses Denison (2000) and for measuring work motivation uses the theory of Abraham Maslow (Robbins, 2008). The reliability of the organizational culture scale is known to be 0.843, while the reliability of the work motivation scale is known to be 0.867. It can be concluded from the research findings on organizational culture and work motivation that both variables have a significant positive relationship with results (r = 0.598; p0.5, which indicates that both variables get results with a significant positive correlation between organizational culture and work motivation